Effect of Roaming Transition States upon Product Branching in the Thermal Decomposition of CH3NO2 - Zhu, R. S; Raghunath, P; Lin, M. C (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2013)
The kinetics for the thermal unimolecular decomposition of CH3NO2 and its structural isomer CH3ONO have been investigated by statistical theory calculations based on the potential energy surface calculated at the UCCSD(T)/CBS and CASPT3(8, 8)/6-311+G(3df,2p) levels. Our results show that for the decomposition of CH3NO2 at pressures less than 2 Torr, isomerization to CH3ONO via the recently located roaming transition state is dominant in the entire temperature range studied, 400–3000 K. However, at higher pressures, the formation of the commonly assumed products, CH3 + NO2, becomes competitive and at pressures higher than 200 Torr the production of CH3 + NO2 is exclusive. The predicted rate constants for 760 Torr and the high-pressure limit with Ar as diluent in the temperature range 500–3000 K, producing solely CH3 + NO2, can be expressed respectively by k d 760(CH3NO2) = 2.94 × 1055 T –12.6 exp(−35500/T) s–1 and k d ∞(CH3NO2) = 5.88 × 1024 T –2.35 exp(−31400/T) s–1. In the low pressure limit, the decomposition reaction takes place exclusively via the roaming TS producing internally excited CH3ONO, giving rise to both CH3O + NO and CH2O + HNO with the second-order rate constant k d 0(CH3NO2) = 1.17 × 1031 T –10.94  exp(−32400/T) cm3 molecule–1 s–1. For CH3ONO decomposition, a new roaming transition state connecting to the CH2O + HNO products has been located, lying 6.8 kcal/mol below the well-known four-member ring tight transition state and 0.7 kcal/mol below CH3O + NO. The rate constants predicted by similar calculations give rise to the following expressions for the thermal decomposition of CH3ONO in He: k d 760(CH3ONO) = 8.75 × 1041 T –8.97 exp(−22600/T) s–1 and k d ∞(CH3ONO) = 1.58 × 1023 T –2.18 exp(−21100/T) s–1 in the temperature range 300–3000 K. These results are in very good agreement with available experimental data obtained under practical pressure conditions. The much different branching ratios for the formation of CH3O + NO and CH2O + HNO in the decomposition of both CH3NO2 and CH3ONO are also given in this work.